Validation of the association of TCF7L2 and SLC30A8 gene polymorphisms with post-transplant diabetes mellitus in Asian Indian population - Hasan, Qurratulain; Rao, Pragna; Khan, IImran Ali; Jahan, Parveen (Intractable & Rare Diseases Research, 2015)
The rs7903146 and rs13266634 polymorphisms in the TCF7L2 and SLC30A8 genes, respectively, have been reported to be associated with type 2 diabetes. However, little is known about the association of these polymorphisms with post-transplant diabetes mellitus (PTDM). To study this linkage, we determined a distribution of allele and genotype frequencies in Asian Indians. 42 PTDM and 98 non-PTDM subjects were recruited. Polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was performed to detect for rs7903146 and rs13266634 polymorphisms. The clinical details and statistical analysis for PTDM and non-PTDM subjects were recorded. Our results observed higher frequencies of the minor alleles in rs7903146 and rs13266634 polymorphisms in the PTDM group compared to the non-PTDM subjects. The allele frequencies also found to be significantly associated with PTDM (rs7903146: T vs C: OR-2.6; (95%CI: 1.2-5.6); p = 0.01; rs13266634: T vs C: OR-2.0; (95%CI: 1.1-3.4); p = 0.01). These findings suggest that rs7903146 and rs13266634 polymorphisms are associated with PTDM in the Asian Indian population despite a relatively small study group.